Evaluation of Robotics Class in a Private School in the Philippines - Ahillon Jr., Ricardo Cruz; Cadiong, Sabella Resanie C.; Tomeldan, Alaric B.; Belgira, Arrah Crisrei B.; Ayaya, Alfonso Rafael A.; Paredes, Althea Dominique M.; Balajadia, Dominick Johan G.; Sumandal, Ron Gabriel F.; Basilio, Lionel Decasa; Quindra, Kaizen C. (ASEAN Journal of Educational Research and Technology, 2025)
The present study aimed to evaluate the robotics class at Ianthe Christian Academy. This present study used descriptive research using a survey. Respondents in the study were parents and learners at Ianthe Christian Academy as they participated in outdoor classes. These are Grade 3 to 6 learners. Samples were chosen from the population using simple random sampling. Parent-respondents were identified using Part I: Profile of the respondents which includes age, sex, and economic status. Part II: Teaching and Part III: Learning describe the teaching and learning on outdoor activities at Ianthe Christian School. The scale described how outdoor activities happened in the school. Findings revealed that parents strongly agreed on Teaching and Learning Robotics Classes, learners performed outstandingly in various subject areas, and there is no relationship between both teaching and learning in the academic performance of learners. Parents were satisfied with the robotics class in school, learners showed enthusiasm and commitment to their subjects taken, and they did not directly affect learners' performance in robotics class. Parents should be engaged in the learning experience of the learners in the robotics class, providing additional worksheets that enhance the skills of learners, and encouraging parents to communicate with teachers.